The effect of firm size, financial performance, listing age and audit quality on Internet Financial Reporting - Mahendri, Ni Wayan Putri; Irwandi, Soni Agus (Universitas Hayam Wuruk Perbanas, 2016)
Financial reporting is the most important information for investors. So far, a rapid internet growth has created a new strategy for companies to communicate with investors. In this case, internet could be used by companies to report their financial information, or commonly known as Internet Financial Reporting (IFR). The objec-tive of this study is to analyze the effect of firm size, profitability, liquidity, leverage, listing age, and auditor reputation on Internet Financial Reporting. The sample, as based on sampling criteria, consists of 82 manufacturing companies listed in the Indonesia Stock Exchange in 2013. This study used a multiple regression analysis for the analyses such as to examine the variables that affect the Internet Financial Reporting. The findings show that firm size has a significant effect on Internet Fi-nancial Reporting. However, other factors such as profitability, liquidity, leverage, listing age, and auditor reputation have no significant effects on Internet Financial Reporting. The implication of this study is that the investors can use this study as a reference related to investment in Indonesia.